Congruence of Ankeny-Artin-Chowla type modulo p^2 - Jakubec, Stanislav; Laššák, Miroslav (Annales Mathematicae Silesianae, 1998)
In this paper the results of [4] and [5] on the congruence of Ankeny-Artin-Chowla type modulo p2 for real subfields of the Q(ζp) of a prime degree l > 2 are simplified to explicit forms (2) and (3) of the Theorem 1. The congruence is then used to calculations of class numbers in special quintic fields and to some calculations in cubic fields.